Lifting the discrepancy between experimental results and the theoretical predictions for the catalytic activity of RuO2(110) towards oxygen evolution reaction. Issue 35 (25th August 2021) - Divanis, Spyridon; Frandsen, Adrian Malthe; Kutlusoy, Tugce; Rossmeisl, Jan
Abstract : The high catalytic activity of RuO2 (110) towards the oxygen evolution reaction is explained theoretically by considering an alternate reaction pathway for this catalyst. Abstract : Developing new efficient catalyst materials for the oxygen evolution reaction (OER) is essential for widespread proton exchange membrane water electrolyzer use. Both RuO2 (110) and IrO2 (110) have been shown to be highly active OER catalysts, however DFT predictions have been unable to explain the high activity of RuO2 . We propose that this discrepancy is due to RuO2 utilizing a different reaction pathway, as compared to the conventional IrO2 pathway. This hypothesis is supported by comparisons between experimental data, DFT data and the proposed reaction model.